Reliability of trunk shape measurements based on 3-D surface reconstructions - Pazos, Valérie (Springer-Verlag, 2007)
This study aimed to estimate the reliability of 3-D trunk surface measurements for the characterization of external asymmetry associated with scoliosis. Repeated trunk surface acquisitions using the Inspeck system (Inspeck Inc., Montreal, Canada), with two different postures A (anatomical position) and B (‘‘clavicle’’ position), were obtained from patients attending a scoliosis clinic. For each acquisition, a 3-D model of the patient’s trunk was built and a series of measurements was computed. For each measure and posture, intraclass correlation coefficients (ICC) were obtained using a bivariate analysis of variance, and the smallest detectable difference was calculated. For posture A, reliability was fair to excellent with ICC from 0.91 to 0.99 (0.85 to 0.99 for the lower bound of the 95% confidence interval). For posture B, the ICC was 0.85 to 0.98 (0.74 to 0.99 for the lower bound of the 95% confidence interval). The smallest statistically significant differences for the maximal back surface rotation was 2.5 and 1.5° for the maximal trunk rotation. Apparent global asymmetry and axial trunk rotation indices were relatively robust to changes in arm posture, both in terms of mean values and within-subject variations, and also showed a good reliability. Computing measurements from cross-sectional analysis enabled a reduction in errors compared to the measurements based on markers’ position. Although not yet sensitive enough to detect small changes for monitoring of curve natural progression, trunk surface analysis can help to document the external asymmetry associated with different types of spinal curves as well as the cosmetic improvement obtained after surgical interventions. The anatomical posture is slightly more reliable as it allows a better coverage of the trunk surface by the digitizing system.